Source Distribution and Ecological Risk Assessments of Heavy Metals from the Soils of Riruwai Mining Area, North-Western Nigeria - Badamasi, Hamza; Dauda, Aminu; Suleiman, Abdullahi Khalil; Muhammad, Sa’adatu Eri; Durumin-Iya, Naseer Inuwa; Abdullahi, Hadiza Usman (Indonesian Journal of Environmental Management and Sustainability, 2024)
Mining is an important global economic driver, contributing to human civilization’s advancement and foreign exchange revenues. However, it causes significant environmental contamination, particularly in developing nations with inadequate waste management and ineffective mining legislation. In the present study, the source distribution and ecological risk of heavy metals (HMs) from the soils of the mining area around Riruwai town, northern Nigeria, were assessed. Soil samples were obtained from active and abandoned mining sites, farmlands, and control sites and were analyzed for physicochemical characteristics and HM contents. The measured concentrations of HMs were used to evaluate the source distribution and ecological risks. The study’s findings indicated that, with the exception of Mn, Hg, and Ni, all HM concentrations were above threshold levels in all sample locations aside from the control sites. The results of the correlation analysis showed that there was a significant correlation between the HMs, indicating that they came from comparable origins. Principal component analysis and hierarchical cluster analysis results indicated that As, Cr, Hg, Ni, and Zn might originate from similar anthropogenic sources, possibly mining activities, while Cd, Mn, and Pb might come from natural sources (parent material). Results of an ecological risk assessment revealed that the soils from active and abandoned mining sites were severely polluted by HMs. The degree of pollution has begun to extend onto farmland, signifying a critical need for adequate HM pollution control in the study area.